Reversible heart failure: toxins, tachycardiomyopathy and mitochondrial abnormalities. Issue 1046 (28th June 2012) - Morris, Paul D; Robinson, Tim; Channer, Kevin S
Abstract : Heart failure is usually a relentless condition associated with a poor prognosis. Triggered by a physiological insult, maladaptive neurohumoral processes result in an ever-spiralling deterioration of cardiovascular function. However, there are certain underlying conditions which are associated with a temporary reduction in contractile function leading to reversible heart failure. These conditions affect a relatively small number of patients when compared with heart failure secondary to inherited cardiomyopathies and ischaemic heart disease. There are two broad mechanisms responsible for reversible myocyte dysfunction: acute inflammatory activation in which cytokines depress myocyte function, and toxic effects in which there is impairment of intra-cellular energetics. In this review, we discuss reversible heart failure caused by toxic effects. These effects can be caused by drugs (prescribed and illicit) and by tachycardic arrhythmia (tachycardiomyopathy), and are caused by abnormalities of mitochondrial function and myocytic calcium processing. The underlying pathological mechanisms, clinical features and management options are discussed, illustrated by clinical case studies.